Purchasing Power Parity and the Canadian Float in the 1950s - Choudhry, Taufiq; McNown, Robert; Wallace, Myles (The Review of Economics and Statistics, 1991)
In this paper, the authors present evidence that neither large differences in inflation nor long time periods are necessary for a finding favorable to purchasing power parity. Evidence from cointegrating regressions and tests of the real exchange rate indicate that purchasing power parity held as a long-run constraint between the United States and Canada for the period 1950:10 to 1961:5. The authors also find that government intervention can distort purchasing power parity over a finite period. Once the data were extended beyond the period of the free float, the evidence is no longer favorable to purchasing power parity. Copyright 1991 by MIT Press.